A Retrospective Study One-Year Survey from COVID-19: Three Waves and Three Patterns in Italy - Kolesova, Olga; Tomassetti, Flaminia; Cerini, Paola; Caldarelli, Laura; Marullo, Laura; Cantore, Fulvio; Zocca, Elena; Frassanito, Maria Loredana; Quarantelli, Maria Teresa; Pieri, Massimo; Calugi, Graziella (Journal of Epidemiology and Public Health, 2021)
Background: Since December 2019 an unprecedented coronavirus pandemic (COVID-19) in Italy and in all the world, has been spreading. This study is a retrospective overview of Italian popula